Women in the gig economy: Paid work, care and flexibility in Kenya and South Africa - Abigail Hunt; Emma Samman; Sherry Tapfuma; Grace Mwaura; Rhoda Omenya (Overseas Development Institute (ODI), 2019)
The gig economy is expanding globally, with exponential growth forecast in traditionally female-dominated sectors - notably on-demand household services including cooking, cleaning and care work. But little research to date has focused on gendered experiences of gig work or on gig workers outside North America and Europe. This report presents findings from an in-depth study of women's engagement in the gig economy in Kenya and South Africa, two middle-income countries at the forefront of developments in digitally mediated work in sub-Saharan Africa. It aims to understand the impact of this engagement on workers' lives, considering the quality of work on offer and its implications for workers' management of paid work and unpaid care and domestic work. The report argues that policy-makers and platform companies should play a central role in ensuring high-quality work, including improving economic security, supporting unpaid work, giving workers more control over schedules, ensuring their safety, and basing policy and practice on worker preferences - which also requires fostering collective action.
Keywords: 330